Boosted hydrogen evolution in alkaline media enabled by a facile oxidation-involving surface modification. (1st December 2021) - Zeng, Liming; Luo, Jing; Mao, Guihong; Wu, Daifeng; Li, Rui; Huang, Ling; Wang, Dongxing; Zhou, Qing; Sun, Tai; Xiao, Fangming; Tang, Renheng
Highlights: A two-step modification strategy was proposed to design efficient HER catalysts. The oxidation treatment involved enables the highly uniform distribution of Pt NPs and fast kinetics of electron transfer and mass transport. The Pt/Ox-U-AB with oxidation treatment demonstrated the superior HER performance in alkaline media. Abstract: Due to the intrinsically sluggish kinetics of hydrogen evolution reaction (HER) in alkaline media, it is of great significance to develop efficient electro-catalyst to improve the reaction kinetics. Herein, a novel designing strategy involving unique two-step chemical modifications on carbon support is proposed and examined for HER catalysis employing the metallic platinum as active species. The physicochemical characterization results shows that the carbon support suffering from oxidation pretreatment prior to adsorption of N-containing ligand molecules enables the highly uniform dispersion of Pt NPs and faster kinetics of electron transfer in comparison to the counterpart with reduction pretreatment. More importantly, the oxidation modification-involving carbon supported platinum catalyst (Pt/Ox-U-AB) displays a quite smaller difference of overpotentials (Δη∼24 mV) between in alkaline and acidic media at 10 mA cm −2 than Pt/Red-U-AB (95 mV) and commercial 20% Pt /C (58 mV) under an equivalent amount of Pt loading (4 μgPt cm geo − 2 ), implying much higher HER performance toward HER in alkaline media. Furthermore, the excellent HER performance of Pt/Ox-U-AB is also revealed by the higher ECSA value (2.51  cm Pt 2 μ g Pt − 1 ) and mass activity (3.98 mA μ g Pt − 1 ) than others. The superior HER performance of Pt/Ox-U-AB in alkaline media can be rationally attributed to the substantial exposure of electrochemically accessible active sites and favorable chemical environment on the catalyst surface endowed by the unique two-step modification involving oxidation pretreatment. The architecting strategy in this work offers a feasible way to design high-performance and cost-effective catalysts toward hydrogen evolution catalysis in alkaline media. Graphical abstract: Image, graphical abstract